Severity of pandemic H1N1 2009 influenza virus infection may not be directly correlated with initial viral load in upper respiratory tract - Wu, Un‐In (Influenza Other Respir Viruses, 2011)
Please cite this paper as: Wu et al. (2012) Severity of pandemic H1N1 2009 influenza virus infection may not be directly correlated with initial viral load in upper respiratory tract. Influenza and Other Respiratory Viruses 6(5), 367–373. Background  Recent studies have demonstrated that rapid influenza diagnostic tests (RIDTs) have a relatively low sensitivity in detecting severe cases of pandemic H1N1 2009 influenza virus (pH1N1) infection. We hypothesized that viral load in upper respiratory specimens obtained on presentation may not be correlated with disease severity. Methods  We conducted a prospective study to compare patterns of viral shedding using nasopharyngeal swab specimens, according to the number of days of post‐symptom onset and post‐antiviral therapy, between patients with and without complications. Results  From July 15, 2009 through July 23, 2010, we collected and processed a total of 141 nasopharyngeal swab specimens from 64 inpatients and outpatients with laboratory‐confirmed pH1N1 infection. These included 46 patients without any complications (uncomplicated group) and 18 patients who required hospital admission (complicated group). The mean initial viral load was higher in the uncomplicated group than in the complicated group (3·4 ± 1·6 log(10) copies/μl versus 1·9 ± 1·7, P = 0·02). However, prolonged viral shedding was only detected in the complicated group (44% by day 7 of antiviral therapy). By multivariate analysis, we found that age (OR, 1·1; 95% CI, 1·0–1·1) and initial nasopharyngeal viral load (OR, 0·5; 95% CI, 0·3–0·8) were significant factors associated with complications. Conclusion  Given that patients with severe pH1N1 infection may have relatively lower initial viral load in the upper respiratory tract, cautious interpretation of negative RIDT results is particularly warranted in this patient population.